2022
DOI: 10.1242/dev.200275
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling regulates neural stem cell quiescence entry and exit in Drosophila

Abstract: Stem cells enter and exit quiescence as part of normal developmental programs and to maintain tissue homeostasis in adulthood. While it is clear that stem cell intrinsic and extrinsic cues, local and systemic, regulate quiescence, it remains unclear whether intrinsic and extrinsic cues coordinate to control quiescence and how cue coordination is achieved. Here, we report that Notch signaling coordinates neuroblast intrinsic temporal programs with extrinsic nutrient cues to regulate quiescence in Drosophila. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Hippo signaling coordinates the restriction of growth during development and the maintenance of stem cell quiescence in Drosophila (Halder & Johnson, 2011; Staley & Irvine, 2012; Ding et al, 2016; Jin et al, 2013). As previously addressed, Notch signaling also plays an important role in maintaining Drosophila stem cell quiescence (Bjornson et al, 2013; Bernard et al, 2010; Sood et al, 2022; Anant et al, 1998). Its reappearance in our RNA-seq reaffirms the importance of this pathway for diapause, well as the robustness of our data.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Hippo signaling coordinates the restriction of growth during development and the maintenance of stem cell quiescence in Drosophila (Halder & Johnson, 2011; Staley & Irvine, 2012; Ding et al, 2016; Jin et al, 2013). As previously addressed, Notch signaling also plays an important role in maintaining Drosophila stem cell quiescence (Bjornson et al, 2013; Bernard et al, 2010; Sood et al, 2022; Anant et al, 1998). Its reappearance in our RNA-seq reaffirms the importance of this pathway for diapause, well as the robustness of our data.…”
Section: Resultsmentioning
confidence: 93%
“…5C). Both pathways are essential to the maintenance of stem cell identity and the induction of cellular quiescence, depending on environmentally and developmentally timed cues (Dey et al, 2016; Firth et al, 2010; Sood et al, 2022). Interestingly, Notch signaling has also been shown control differentiation through its effects on fatty acid metabolism (Garcés et al, 1997; Jabs et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also reported that Notch activity becomes attenuated in quiescent CB NBs because CB NBs are no longer dividing and producing Delta-expressing GMC daughters for Notch pathway transactivation. Moreover, low Notch is necessary for CB NBs to reactivate from quiescence in response to dietary nutrients (Sood et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Cleaved Notch ICD (intracellular domain) relocates to the nucleus where it binds to Suppressor of Hairless [Su(H)] and Mastermind to regulate gene expression (Rebay et al, 1991; Fortini and Artavanis-Tsakonas, 1994; Pan and Rubin, 1997; Strooper et al, 1999; Mumm et al, 2000; Kitagawa et al, 2001; Kopan and Ilagan, 2009). We recently reported that Notch signaling regulates CB NB quiescence during the embryonic to larval transition (Sood et al, 2022). When Notch is knocked down, some CB NBs continue dividing during this transition.…”
Section: Introductionmentioning
confidence: 99%